2011
DOI: 10.1016/j.physa.2010.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Sales distribution of consumer electronics

Abstract: a b s t r a c tUsing the uniform most powerful unbiased test, we observed the sales distribution of consumer electronics in Japan on a daily basis and report that it follows both a lognormal distribution and a power-law distribution and depends on the state of the market. We show that these switches occur quite often. The underlying sales dynamics found between both periods nicely matched a multiplicative process. However, even though the multiplicative term in the process displays a size-dependent relationshi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…However, this calculation still suggests a way to reconcile the different empirical estimates of power-law exponents for tangible fixed assets, the number of workers, and annual sales. See Mizuno et al (2011) for more empirical results and discussion along this line of research.…”
Section: Resultsmentioning
confidence: 99%
“…However, this calculation still suggests a way to reconcile the different empirical estimates of power-law exponents for tangible fixed assets, the number of workers, and annual sales. See Mizuno et al (2011) for more empirical results and discussion along this line of research.…”
Section: Resultsmentioning
confidence: 99%
“…Market share was defined by the daily sales volume of a generic product such as "digital camera", "mouse", and so on. Note also that to keep consistency with Hisano and Mizuno [31], we only analyzed products which are "alive" by the definition described below when analyzing market share distributions. Products shown in Fig.…”
Section: Validation Of the Model Assumptionsmentioning
confidence: 99%
“…Hisano and Mizuno [31] analyzed the same data set and reported that the asymptotic behavior of the market The lower threshold for the validity of the power law tail of the distribution was estimated using the method described in Ref. [31].…”
Section: Tests Of the Theoreticalmentioning
confidence: 99%
“…Chevalier and Goolsbee (2003) used a power law function to describe online books sales, while Hisano and Mizuno (2011) observed that the sales distribution of consumer electronics follows both power law and log-normal distributions. Stanley et al (1995) used a log-normal distribution to fit the size distribution of firms.…”
Section: Introductionmentioning
confidence: 99%